A cross-sectional study on oral health-care habits and oral-health-related quality-of-life in marginalized persons in Copenhagen - Esben Boeskov Øzhayat; Ashraf Elmongy; Lene Tanderup; Sine Lykke Bordorff; Henrik Thiesen (Medical Journals Sweden, 2024)
Objective: The aim of this cross-sectional study was to investigate the oral-health-related quality-of-life (OHRQoL) and oral health-care habits in a population of marginalized persons in Copenhagen. Materials and Methods: Patients attending a dental clinic for marginalized persons filled in the 14-item version of the oral-health-impact profile (OHIP-14) regarding their OHRQoLand a questionnaire on their oral health-care habits. Age, gender, smoking habits, need for general and oral health-care, and living conditions were further registered. Results: Of the 212 participants, 72% had not visited a dental clinic within the past two years and in 68% of the cases, the last dental visit was related to dental treatment. Tooth brushing at least once a day was reported by 93%. The mean OHIP-14 score in the participants was 24.9 (SD: 13.6). The most frequent problems were pain, chewing difficulties, being self-conscious, tense, and embarrassed as well as affected life. The mean OHIP-14 score was significantly higher in participants in need of general health-care (29.5, SD: 12.2) than in participants not in need of general health-care (22.8, SD: 13.9). The same applied to participants referred for dental treatment (26.1, SD: 12.7) compared to participants not being referred (20.2, SD: 15.9). Conclusions: The OHRQoLis poor in the population with pain, chewing difficulties and aesthetic issues as the most prominent problems. The participants had low and treatment-oriented use of the dental care system. This indicates a high need for dental care in the population with a focus on including them in the dental care system.